Analisis Strategi Usaha Laundry di Queen A & K Laundry Syariah Menggunakan Model Balanced Scorecard - Tiara Indah Nirwana; Mhd. Rahmat Hidayat (Indo Publishing, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, contributing over 60% to Gross Domestic Product (GDP) and employing over 97% of the national workforce. Laundry, as a service sector for MSMEs, has experienced growth in line with changes in modern lifestyles that require practical and efficient laundry services. Laundry A & K Laundry Syariah in Meulaboh, West Aceh, consistently adopts sharia principles in its operations, including honest weighing, price transparency, and the implementation of digital scales and digital financial records, which increase efficiency and customer trust. The study used qualitative descriptive methods and the Balanced Scorecard model to analyze business strategies from the perspectives of finance, customers, internal processes, and learning and growth. The results show that the implemented strategy is effective, with a high repeat order rate, stable cost control, and internal processes that comply with sharia standard operating procedures. Recommendations are directed at strengthening digital promotions and developing production facilities to expand market share and increase competitiveness..